Evolution of gamete attraction molecules: evidence for purifying selection in speract and its receptor, in the pantropical sea urchin Diadema. Issue 1 (January 2015) - Jagadeeshan, Santosh; Coppard, Simon E.; Lessios, Harilaos A.
SUMMARY Many free‐spawning marine invertebrates, such as sea urchins, lack any courtship or assortative mating behavior. Mate recognition in such cases occur at the gametic level, and molecules present on the sperm and egg are major determinants of species‐specific fertilization. These molecules must also coevolve in relation to each other in order to preserve functional integrity. When sea urchins release their gametes in seawater, diffusible molecules from the egg, termed sperm‐activating peptides, activate and attract the sperm to swim toward the egg, initiating a series of interactions between the gametes. Although the compositions and diversity of such sperm‐activating peptides have been characterized in a variety of sea urchins, little is known about the evolution of their genes. Here we characterize the genes encoding the sperm‐activating peptide of the egg (speract) and its receptor on the sperm, and examine their evolutionary dynamics in the sea urchin genus Diadema, in the interest of determining whether they are involved in reproductive isolation between the species. We found evidence of purifying selection on several codon sites in both molecules and of selectively neutral evolution in others. The diffusible speract peptide that activates sperm is invariant across species, indicating that Diadema egg peptides do not discriminate between con‐ and hetero‐specific sperm at this stage of the process. Speract and its receptor do not contribute to reproductive isolation in Diadema.